A review of site-controlled compound semiconductor quantum dots for single photon emitters - Yaonan Hou (Materials for Quantum Technology)
Single photon emitters (SPEs) serve as the fundamental building blocks of photonic networks for applications in quantum information science and technology. This review paper focuses specifically on the rapidly growing area of site-controlled and deterministically fabricated compound semiconductor quantum dots (QDs), which holds great potential for scalability given their high quantum efficiency, flexible coherence tunability and compatibility with silicon photonics. In this paper, the state-of-the-art growth and fabrication approaches, integration with photonic structures have been reviewed. Meanwhile, the emission properties from QD-based SPEs, including brightness, purity and coherence tunability, have been discussed. This review also provides an outlook of future developments of site-controlled QDs, offering insights into the progress toward scalable quantum photonic systems.